Synergetic stability enhancement with magnesium and calcium ion substitution for Ni/Mn-based P2-type sodium-ion battery cathodes. Issue 3 (23rd December 2021) - Fu, Hongwei; Wang, Yun-Peng; Fan, Guozheng; Guo, Shan; Xie, Xuesong; Cao, Xinxin; Lu, Bingan; Long, Mengqiu; Zhou, Jiang; Liang, Shuquan
Abstract : A synergetic effect involving Mg and Ca can reduce the adverse impact on redox reactions related to Ni–O bonding in Mg and Ca co-doped P2-Na0.67 Ni0.33 Mn0.66 O2 material, leading to better overall properties than its singly-doped counterparts. Abstract : The conventional P2-type cathode material Na0.67 Ni0.33 Mn0.67 O2 suffers from an irreversible P2–O2 phase transition and serious capacity fading during cycling. Here, we successfully carry out magnesium and calcium ion doping into the transition-metal layers (TM layers) and the alkali-metal layers (AM layers), respectively, of Na0.67 Ni0.33 Mn0.67 O2 . Both Mg and Ca doping can reduce O-type stacking in the high-voltage region, leading to enhanced cycling endurance, however, this is associated with a decrease in capacity. The results of density functional theory (DFT) studies reveal that the introduction of Mg 2+ and Ca 2+ make high-voltage reactions (oxygen redox and Ni 4+ /Ni 3+ redox reactions) less accessible. Thanks to the synergetic effect of co-doping with Mg 2+ and Ca 2+ ions, the adverse effects on high-voltage reactions involving Ni–O bonding are limited, and the structural stability is further enhanced. The finally obtained P2-type Na0.62 Ca0.025 Ni0.28 Mg0.05 Mn0.67 O2 exhibits a satisfactory initial energy density of 468.2 W h kg −1 and good capacity retention of 83% after 100 cycles at 50 mA g −1 within the voltage range of 2.2–4.35 V. This work deepens our understanding of the specific effects of Mg 2+ and Ca 2+ dopants and provides a stability-enhancing strategy utilizing abundant alkaline earth elements.